Al2O3 Nanoparticulate LZS Glass–Ceramic Matrix Composites for Production of Multilayered Materials. Issue 11 (28th July 2016) - Arcaro, Sabrina; Isabel Nieto, Maria; Rodrigues Neto, João B.; Novaes de Oliveira, Antonio Pedro; Moreno, Rodrigo
Abstract : This work reports the processing steps of Al2 O3 (1–5 vol%) nanoparticulate ( d V.50 = 13 nm) LZS glass–ceramic matrix (19.58Li2 O·11.10ZrO2 ·69.32SiO2, mol%, d v.50 = 3.5 μm) composites for production of multilayered materials with thermal expansion gradients obtained by tape casting. Suspensions were prepared in water to solids contents ranging from 40 to 47 vol% using ammonium polyacrylate as a deflocculant, and an acrylic copolymer and polyvinyl alcohol as binders. Optimum performance was achieved by sonication and controlling the rheological properties for every step of the process. To prepare the composites, different concentrations (1, 2.5 and 5 vol%) of nanoalumina were added to fresh, as‐prepared LZS suspensions, by changing the solid contents as required to maintain similar viscosities. Green tapes with high uniformity, without macroscopic defects and easy to handle were sintered to relative densities between 89% and 94%. Dense and homogeneous laminates with gradual composition with increasing concentrations of alumina were obtained.